2008
DOI: 10.1038/onc.2008.318
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of androgen receptor transcriptional activity by rapamycin in prostate cancer cell proliferation and survival

Abstract: The mTOR (mammalian target of rapamycin) inhibitor rapamycin caused growth arrest in both androgendependent and androgen-independent prostate cancer cells; however, long-term treatment induced resistance to the drug. The aim of this study was to investigate methods that can overcome this resistance. Here, we show that rapamycin treatment stimulated androgen receptor (AR) transcriptional activity, whereas suppression of AR activity with the antiandrogen bicalutamide sensitized androgen-dependent, as well as AR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 29 publications
13
75
0
1
Order By: Relevance
“…S6A). Similar adverse effects have been shown among other mTOR inhibitors, such as RAD001 and rapamycin (1,3). Combining DHT with NVP-BEZ235 effectively prevents this elevation in AKT phosphorylation (Supplementary Fig.…”
Section: Armentioning
confidence: 62%
See 3 more Smart Citations
“…S6A). Similar adverse effects have been shown among other mTOR inhibitors, such as RAD001 and rapamycin (1,3). Combining DHT with NVP-BEZ235 effectively prevents this elevation in AKT phosphorylation (Supplementary Fig.…”
Section: Armentioning
confidence: 62%
“…For example, combining the ER inhibitor tamoxifen and a PI3K inhibitor in breast cancers achieves a better therapeutic effect than either single drug alone (34). Studies have also shown that combination of mTOR inhibitors and AR antagonists could effectively treat advanced prostate cancer (1,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colin also showed a synergistic effect of the combination of the anti-androgen bicalutamide, and the mTOR inhibitor rapamycin in CaP cell lines (Wang et al 2008). The basic premise was that in non-tumor prostate, the mTOR pathway promotes AR transcriptional activity, whereas in castration-resistant tissue, mTOR has the opposite effect.…”
Section: Cancer Biologymentioning
confidence: 99%